Macroscale adhesion of gecko setae reflects nanoscale differences in subsurface composition - Loskill, Peter; Puthoff, Jonathan; Wilkinson, Matt; Mecke, Klaus; Jacobs, Karin; Autumn, Kellar (Journal of the Royal Society Interface, 2013)
Surface energies are commonly used to determine the adhesion forces between materials. However, the component of surface energy derived from long-range forces, such as van der Waals forces, depends on the material's structure below the outermost atomic layers. Previous theoretical results and indirect experimental evidence suggest that the van der Waals energies of subsurface layers will influence interfacial adhesion forces. We discovered that nanometre-scale differences in the oxide layer thickness of silicon wafers result in significant macroscale differences in the adhesion of isolated gecko setal arrays. Si/SiO2 bilayer materials exhibited stronger adhesion when the SiO2 layer is thin (approx. 2 nm). To further explore how layered materials influence adhesion, we functionalized similar substrates with an octadecyltrichlorosilane monolayer and again identified a significant influence of the SiO2 layer thickness on adhesion. Our theoretical calculations describe how variation in the SiO2 layer thickness produces differences in the van der Waals interaction potential, and these differences are reflected in the adhesion mechanics. Setal arrays used as tribological probes provide the first empirical evidence that the 'subsurface energy' of inhomogeneous materials influences the macroscopic surface forces.
Keywords: van der Waals forces; gecko adhesion; surface energy